2014
DOI: 10.1186/1471-2164-15-784
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of ETV6 and CDKN1B in patients with acute myeloid leukemia and complex karyotype

Abstract: BackgroundAcute myeloid leukemia with complex karyotype (CK-AML) is a distinct biological entity associated with a very poor outcome. Since complex karyotypes frequently contain deletions of the chromosomal region 12p13 encompassing the tumor suppressor genes ETV6 and CDKN1B, we aimed to unravel their modes of inactivation in CK-AML.ResultsTo decipher deletions, mutations and methylation of ETV6 and CDKN1B, arrayCGH, SNP arrays, direct sequencing of all coding exons and pyrosequencing of the 5′UTR CpG islands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Labelling and hybridization of genomic DNA were performed according to the protocol provided by Agilent without enzymatic restriction. Data visualization and analysis was performed as described [ 13 ]. Copy number profiling for patient 8 was performed on a 60K oligonucleotide array (Agilent Technologies, Diegem, Belgium) according to the manufacturer’s instructions with minor modifications as described [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Labelling and hybridization of genomic DNA were performed according to the protocol provided by Agilent without enzymatic restriction. Data visualization and analysis was performed as described [ 13 ]. Copy number profiling for patient 8 was performed on a 60K oligonucleotide array (Agilent Technologies, Diegem, Belgium) according to the manufacturer’s instructions with minor modifications as described [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…It can be guessed that this partial deletion results in a decreased expression of this gene [11]. These authors demonstrated that levels of ETV6 were significantly decreased in cases with 12p13 deletions encompassing the entire gene or at least the 3'UTR, like in the present case, whereas expression of other genes in the deleted region, like BCL2L14, LRP6, DUSP16 and GPRC5D, did not show any variation, independently of their copy number status.…”
Section: Discussionmentioning
confidence: 47%
“…Other genes within the minimal deleted region like CDKN1B, BCL2L14, LRP6, DUSP16 and GPRC5D may play an additional role in tumorigenesis and leukemogenesis [11]. All these genes are deleted in the case here presented; his deletion extends to band p11.23 where the oncogene KRAS2 is harbored.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Likewise, somatic ETV6 mutations in AML are rare but recurrent events [7,9]. Deletions involving the cytogenetic region 12p13 are common in hematopoietic malignancies of both lymphoid and myeloid origin, notably in MDS with monosomy 7 [10] and AML with complex karyotypes [11][12][13][14].…”
Section: Etv6-gene Function and Its Importance In Hematopoiesismentioning
confidence: 99%